Forward with basics: enkele recente kerkelijke ontwikkelingen in het licht van de synode van Emden 1571 - Jong, K. W. de (Kerk en theologie, 2022)
This article discusses some recent developments in the Protestant Church in the Netherlands in the light of the decisions of the Synod of Emden (1571), in particular Article 1 of its Acta.